Analisis dan Perancangan Sistem Informasi Kesiswaan Kursus Pemrograman (Studi Kasus: Clevio Coder Camp) - Aries Satryadhi Aldana; Adam Hendra Brata; Eriq Muhammad Adams Jonemaro (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Based on the results of interviews of researchers with the owner of Clevio Coder Camp, one of the obstacles faced was communication from Clevio Coder Camp with parents of students, especially students who came from the collaboration class, because in some schools working with Clevio Coder Camp did not provide access directly between parents and Cevio Coder Camp. Clevio Coder Camp needs an overview of the system to deal with student management problems and communication with students' parents so that good communication can be established to ensure students learn skillfully and get the best for their character and personal development. In this research, we discuss how to design a system that is suitable for Clevio Coder Camp. The design carried out is the design of architecture, components, databases, and interfaces. The design of this application has been tested using Traceability Matrix, CBO, RFC, LCOM1 metrics, and LCOM2 metrics. The results of this application design have a low coupling and high understandability based on CBO and RFC, and cohesion that is based on LCOM1. The design results also have a high adaptability because it meets the adaptable values ​​of CBO and RFC, and meets LCOM2 values ​​0 to 1. In addition, all artifacts are made based on the use case that was made before, because every column and row in the traceability matrix has a value.